New combinations in Aeridinae (Orchidaceae) - Kocyan, Alexander; Schuiteman, André (Phytotaxa, 2014)
New combinations are made in the genera Arachnis, Brachypeza, Dimorphorchis, Grosourdya, Phalaenopsis, Renanthera, Robiquetia, Taeniophyllum, Thrixspermum, Trachoma and Trichoglottis. Two new subgenera are established in Phalaenopsis (subgen. Ornithochilus and Hygrochilus). These changes are proposed to begin aligning the genera recognized in subtribe Aeridinae with results of recent DNA analyses (published elsewhere).